(3GdeSJWQa ef cd af eSJXQas - (3GdCHTjgj, CHh GdaJM, TgGH GdOjf, eMeO Hf CMeO Hf efUhQ, J(B852(3g`s ((3hGOj SjOfG YHO Gddg Hf GdYHGSs)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdYXje hHYO agPg agQSI GdLRA GdKGfj ef GdeSJWQa ef cd af eSJXQa GdHGH GdChd ef GdLRA GdKGfj hgh GdHGH GdNeShf aj PcQ GdZfGA hMH GdeGd hGdGaJNGQ HLeYg heG CTHg Pdcs
(3BNQgG (B:s
(3ah Gddg dh Cf GdHMGQ eOGOG hGdfHGJ CbdGeG hLejY GdNdGFb JcJH eYLRGJg deG bOQhG Ydi MUQ HYV HYV eYLRGJg Udi Gddg Ydjg hSdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 332s
(3eYLe GdeDdajf(B: 3 / 110s
(3cTa GdXfhf(B: 2 / 1674s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs